Psychological Autopsy Study of Suicides among Elderly - Nadaf, Aadamali; Mugadlimath, Anand; P S, Chidananda; Manjunath , K H (Journal of Indian Academy of Forensic Medicine, 2014)
A great deal of research has been focused on the suicide in young, but surprisingly limited  research has been under taken in the area of suicide in elderly accomplished by under reporting. Since  the proportion of older people in population is rising worldwide, indeed the increase in developing  countries like India is even greater than the developed countries. This prospective and descriptive study  among elder people has been carried out in the Department of Forensic Medicine, Victoria Hospital,  Bangalore Medical College and Research Institute, Bangalore during the period November 2005 to April  2007 (18 months). All the cases aged 60 years and above brought to the department for medico-legal  autopsy with alleged history of suicide and or detected as suicide by the circumstantial evidences and  autopsy findings were selected. A sum total of 70 cases were studied during the study period.
Keywords: Elderly suicide; Reasons for suicide; Depression; Psychological autopsy